A new species of Calea (Asteraceae—Neurolaeneae) from Goiás State, Brazil - Lima Da Silva, Gustavo Henrique; Bringel Jr., João Bernardo De Azevedo; Teles, Aristônio Magalhães (Phytotaxa, 2016)
A new species of Calea sect. Monanthocalea (Neurolaeneae, Asteraceae) is here described as C. aldamoides, an endemic species from Goiás State, Brazil. This new species is recognized by the petiolate lanceolate leaves with suprabasal acrodromous venation, and by the terminal radiate capitula. It is closely related to C. abbreviata and C. multiplinervia, and differs from both mainly by the size and margins of the leaves, and the number of the ray florets; it also differs from C. multiplinervia by the size of the pappus scales. Illustrations, comments, distribution map, and conservation status are provided for the new species. Additionally, a diagnostic key to the Brazilian’s Central-West species of C. sect. Monanthocalea is provided.